Adsorption and seepage properties of permeable reaction barrier construction materials for underground coal gasification - WANG Fan; XV Bing; CHEN Lunjian; XING Baolin; SU Faqiang (矿业科学学报, 2024)
Groundwater pollution induced by Underground Coal Gasification(UCG)seriously hinders its development.Permeable Reactive Barrier(PRB)remediation therefore stands out as a major research focus for in-situ groundwater remediation, where the characteristics of PRB material is crucial to their effective operation.This study thus examines the adsorption properties of sand, organic bentonite, and activated carbon on phenol, a characteristic organic pollutant associated with UCG.A self-constructed permeation experimental system is employed to study the adsorption and permeation characteristics of sand, organic bentonite, activated carbon, mixtures of sand and organic bentonite, as well as sand and activated carbon to investigate their comprehensive impact in purifying contaminated water.The results indicate that: ①Organic bentonite exhibits a rapid adsorption rate for phenol in solution, reaching adsorption equilibrium within 10 minutes, despite a relatively low adsorption capacity(1.98 mg/g). Activated carbon, on the other hand, demonstrates a slower adsorption rate yet a higher adsorption capacity(2.22 mg/g).②The adsorption of phenol by organic bentonite conforms to the Freundlich isotherm model, with parameters kF = 0.040 and n = 1.207.Activated carbon follows the Langmuir isotherm model, with parameters Smax = 2.44 mg/g and kL= 0.125 L/mg.③The permeability coefficients of sand and activated carbon are 1.006×10-3 m/s and 4.761×10-2 m/s, respectively.The mixture of sand with activated carbon or organic bentonite could effectively moderate the permeability of the mixed material.When the mass ratio of sand to organic bentonite increases from 1∶1 to 3∶1, the permeability coefficient of the mixed material increases from 2.624×10-6 to 3.468×10-5 m/s.Conversely, when the ratio of sand to activated carbon increases from 1∶1 to 3∶1, the permeability coefficient of the mixed material decreases from 1.379×10-3 to 1.301×10-4 m/s.